Online Tracking Nutrition and Health of High School Students - Dilmen, Haluk; Ertam, Fatih (Aytekin İŞMAN, 2013)
Nutrition and proper diet plays critic role on development of the high school students. During school age disorders due to diet of student may cause problems and open door to the some other diseases. Early detecting and tracking disorders may play important role on the youth health. We find Body Mass Index (BMI) would be relevant in our work in order to diagnose and keep track of disorders. We built computer program called Tracking Nutrition and Health (TNH) especially for high school students and kept track of height, weight, age of students to measure disorders. BMI values outside of the certain range are considered as a sign of disorder. In order to overcome disorders some tips and suggestions are given such as diet plans, exercises and etc. Activities and suggestions are being kept on the system and progress is analyzed over time to make decisions and observe progress that has been made. In this paper limitations, advantages and disadvantages of the proposed method is going to be discussed. Furthermore we will address experience, knowledge and skills we gained through implementations and research